DNA Double-Strand Break Repair as Determinant of Cellular Radiosensitivity to Killing and Target in Radiation Therapy - Mladenov, Emil; Magin, Simon; Soni, Aashish; Iliakis, George (Frontiers in Oncology, 2013)
Radiation therapy plays an important role in the management of a wide range of cancers. Besides innovations in the physical application of radiation dose, radiation therapy is likely to benefit from novel approaches exploiting differences in radiation response between normal and tumor cells. While ionizing radiation (IR)* induces a variety of DNA lesions, including base damages and single-strand breaks (SSBs), the DNA double-strand break (DSB) is widely considered as the lesion responsible not only for the aimed cell killing of tumor cells, but also for the general genomic instability that leads to the development of secondary cancers among normal cells. Homologous recombination repair (HRR), non-homologous end-joining (NHEJ) and alternative NHEJ, operating as a backup, are the major pathways utilized by cells for the processing of DSBs. Therefore, their function represents a major mechanism of radiation resistance in tumor cells. HRR is also required to overcome replication stress - a potent contributor to genomic instability that fuels cancer development. HRR and alternative NHEJ show strong cell cycle dependency and are likely to benefit from radiation therapy mediated redistribution of tumor cells throughout the cell cycle. Moreover, the synthetic lethality phenotype documented between HRR deficiency and PARP inhibition has opened new avenues for targeted therapies. These observations make HRR a particularly intriguing target for treatments aiming to improve the efficacy of radiation therapy. Here, we briefly describe the major pathways of DSB repair and review their possible contribution to cancer cell radioresistance. Finally, we discuss promising alternatives for targeting DSB repair to improve radiation therapy and cancer treatment.